Kajian Yuridis Pengesampingan Pasal 1266 dan Pasal 1267 Kitab Undang -Undang Hukum Perdata sebagai Syarat Batal dalam Perjanjian Kredit Perbankan - Rocky Marciano Ambar; Budi Santoso; Hanif Nur Widhiyanti (Faculty of Law Hang Tuah University, 2017)
Banks in credit agreements use more standard agreements, standard contracts in 2 (two) things, (1) There is an unbalanced position between banks and debtors, banks that have a more dominant position and debtors. (2) There is an understanding of the principle of freedom of contracting and without limits. The Bank has the freedom to seek the form and content of the agreement. Code of Ethics in agreement. The provisions of the Civil Code provide types of compensation for parties. Based on the background, then for problems the problem is written (1). Does the inclusion of Article 1266 and Article 1267 of the Civil Code on the banking system have collected the principles of balance and justice. (2) What are the legal implications of the exclusion clause. The research method is normative juridical research. The result of this research is the neglect of civil law and the principle of compensation is the principle of balance. The basic principle according to Rawls is that it is unfair or more people. in the sense of